CRITICAL SUCCESS FACTORS OF AGILE SOFTWARE DEVELOPMENT IN WATERFALL PROJECT: A CASE STUDY APPROACH - Indra Bayu; Teguh Raharjo; Bob Hardian Syahbuddin (LPPM Nusa Mandiri, 2024)
The evolution of software development methodologies has seen Agile rise in response to the limitations of traditional approaches like Waterfall, characterized by its iterative, collaborative, and adaptable nature. However, integrating Agile within the rigid, structured frameworks of organizations accustomed to Waterfall presents significant challenges. This study addresses how to effectively combine these methodologies to mitigate conflicts and achieve successful project outcomes by identifying and analyzing the Critical Success Factors (CSFs) that enable a harmonious integration of Agile into Waterfall environments. Conducted at PT ABC, a firm balancing formal client interactions and contract creation with internal adoption of Scrum, this research uses the Analytic Hierarchy Process (AHP) to systematically prioritize CSFs through literature review, questionnaire development, data collection, and pairwise comparison analysis. The findings reveal that